Petits riens sophocléens : Antigone II: (V. 162–169, 189–190, 203–204, 207–208, 241–242, 253–254, 289–290, 320–321, 370–375, 389–390, 392–393, 413–414, 444–445, 497–501) - Liberman, Gauthier (Hyperboreus, 2023)
This is the second of ﬁve sets of text-critical, exegetical and sometimes metrical remarks on Antigone. These *Sophocleuncula are not only minute philological notes but they involve broader issues having a bearing on the interpretation and meaning of the drama as a whole. These remarks were composed with a view to drawing attention to a number of forgotten or unseen diﬃculties and to trying to address a number of seen but unsolved problems more eﬃcaciously. The text and meaning of not a few other passages from other works of Sophocles or of other writers (e.g. Aeschylus’ Agamemnon) are also dealt with.